2019
DOI: 10.1097/md.0000000000014860
|View full text |Cite
|
Sign up to set email alerts
|

Panel-based NGS reveals disease-causing mutations in hearing loss patients using BGISEQ-500 platform

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The diagnostic yield of the targeted NGS genetic examination is approaching the reported ratio (i.e., one-half to two-thirds) of HHI in pediatric SNHI [4]. To date, several NGS-based diagnostic panels for HHI, including ours, have been designed [4,45,46,47,48,49]. There is solid evidence that the use of the NGS technique can significantly increase the diagnostic yield of genetic examination for HHI and facilitate the genetic counseling for the affected families.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic yield of the targeted NGS genetic examination is approaching the reported ratio (i.e., one-half to two-thirds) of HHI in pediatric SNHI [4]. To date, several NGS-based diagnostic panels for HHI, including ours, have been designed [4,45,46,47,48,49]. There is solid evidence that the use of the NGS technique can significantly increase the diagnostic yield of genetic examination for HHI and facilitate the genetic counseling for the affected families.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the MGISEQ-2000 currently generates 1.44 TB of sequence data in a single run with a running cost of 10 USD/GB. Several recent studies have compared the performance of BGI sequencers with Illumina’s sequencers and showed that the BGI sequencers produced high-quality sequence data at lower or similar prices in studies of whole-exome [2,3], whole-genome [4][1], transcriptome [5,6], single-cell transcriptome [2,78], metagenome [9], and small RNA sequencing [10].…”
Section: Introductionmentioning
confidence: 99%
“…Though GJB2 is the most common mutation worldwide in different populations, other important genes include SLC26A4, GJB3, GJB6, MYO15A, MYO7A, TMC1, CDH23 etc. were also identified in the pathogenesis of NSHL [24][25][26][27][28]. This study reviewed all the described target genes identified experimentally in NSHL during the period between 2009 and 2020 and attempted to study the interactions between them through functional network analysis and identify the possible deleterious variants.…”
Section: Discussionmentioning
confidence: 99%